Notes on the Road Station and Settlement Vindenis on the Route Naisus-Lisus (An example from the first half of the 4th century) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The paper discusses the data on the issues of ubication of the road station Vindenis on the route Naisus (Niš) – Lisus (Lješ). The opinion of the researchers on the ubication of the settlement and station are quite different. The various directions of the route implied the differences in ubication of the road station Vindenis. The bigger strikink building was discovered on the mentioned route Naisus–Lisus near the village Glavnik (locality Poljanice). It is a villa in which the rooms were heated by the warm air. The rooms were luxurious with the floor mosaic representations. The movable archaeological findings (ceramic vessels, glass, nails, jewellery, money of the Constantine I and Constantine II) date from the first half of the 4th century. However, we believe that the past claims on the ubication of the station Vendenis in Vidin (a part of the village Marevice, near Novo Brdo) are not well founded. It was believed so because of the similarity of name, on the basis of the medieval sources. According to the insight into the terrain, the distances noted in Tabula Peutingeriana Ptolemy’s Geographia, and to the preserved segments of the road and milestones without inscriptions it can be said that the road station Vindenis was situated near Podujevo (five kilometres southwest from Podujevo, and north from Priština), near the village Glavnik (locality Poljanice) behind the left bank of the river Laba. Although the significant number of findings indicates the hypothesis that Vindenis station was in locality Poljanice (Glavnik) near Podujevo, it requires the systematic archaeological researches which would prove it or not.